PENGEMBANGAN MANAJEMEN SISTEM INFORMASI PONDOK PESANTREN (Pemberdayaan Santri Pondok Pesantren Al-Mahrusiyah Lirboyo Kediri) - Musyafa Fathoni; Kadi Kadi; Nu'man Hakiem (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2019)
AbstractFor educational institutions that have many students such as the Pesantren Al Mahrusiyah Lirboyo, implementing computerized management information system is a necessity and importance. By using traditional management, official board and madrasah administrators difficult to submit reports to the kiyai as the top leader of pesantren. These difficulties include delays in data collection and inaccurate data analysis. To manage around 3791 santri located in three different places, pesantren al mahrusiyah lirboyo requires an appropriate computer-based Management Information System and in accordance with the pesantren learning culture. By using Research and Development (R & D) methods this empowerment program produces several things; First, changes in the data processing paradigm through information technology literacy which includes (1) Information Literacy, (2) Computer Literacy, (3) Internet Literacy, and (4) digital literacy. Second, changes in the flow of data management. Third, the realization of an integrated computer-based management information system for pesantren.Keywords: Management Information Systems, Islamic Boarding Schools, Literacy